2017
DOI: 10.3389/fped.2017.00228
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence and Short-term Outcomes of Acute Respiratory Illness with Cough in Children from a Socioeconomically Disadvantaged Urban Community in Australia: A Community-Based Prospective Cohort Study

Abstract: BackgroundAcute respiratory illnesses with cough (ARIwC) are predominant causes of morbidity in Australian Indigenous children; however, data on disease burden in urban communities are scarce. This study aimed to determine the incidence of ARIwC, the predictors of recurrent (≥4 episodes) ARIwC, and development of chronic cough following an ARIwC in urban, predominantly Indigenous, children aged <5 years from northern Brisbane, Australia.MethodsProspective cohort study of children aged <5 years registered with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 46 publications
3
26
0
Order By: Relevance
“…When including all children in the analysis, the prevalence of chronic cough post-acute cough in our study is similar to the 20-26% identified in other studies in South-East Queensland using the same methods and similar communities (6,10). Our study supports the findings of those studies with respect to risk factors for chronic cough (10,22), including preterm birth, illness duration at presentation and childcare. Preterm birth has been associated with a range of both acute and chronic respiratory illnesses (23,24).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…When including all children in the analysis, the prevalence of chronic cough post-acute cough in our study is similar to the 20-26% identified in other studies in South-East Queensland using the same methods and similar communities (6,10). Our study supports the findings of those studies with respect to risk factors for chronic cough (10,22), including preterm birth, illness duration at presentation and childcare. Preterm birth has been associated with a range of both acute and chronic respiratory illnesses (23,24).…”
Section: Discussionsupporting
confidence: 89%
“…However, although primary-care studies have reported 10% of children with an ARI are still coughing after day-25 (9), there are little data on the predictors of chronic cough in children. In our previous study, restricted to a single low-socioeconomic site, predictors of chronic cough were age <12-months, eczema, childcare attendance, previous history of chronic cough, parental Indigenous status, and low income (10). However, generalizability of these data is limited.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Parents are often disturbed by cough and ask that "something is done." In a prospective study in Australian children, a high proportion of parents thought antibiotics should be given for post-infectious cough (34%) or were unsure (24%); surprisingly, antibiotics were prescribed in 14% of episodes characterized by isolated dry cough with no fever (46). Postinfectious cough is difficult to distinguish from PBB and this may complicate therapeutic decisions (9).…”
Section: Discussionmentioning
confidence: 99%
“…Infancy is a critical time to detect, and effectively manage respiratory illness. While up to 6 episodes of self-limiting respiratory illness is normal in the rst year of life (11,12), untreated chronic symptoms commonly lead to lifelong disease, poor quality of life and early death (10). Respiratory illnesses can be split into upper and lower.…”
Section: Introductionmentioning
confidence: 99%